Effects of Air Pollution and Meteorological Conditions on DED: Associated Manifestations and Underlying Mechanisms - Zhou, Hui-Zhong; Liu, Xiufen; Zhou, Dandan; Shao, Fei; Li, Qian; Li, Dan; He, Tianlong; Ren, Yu; Lu, Cheng-Wei (Klinische Monatsblätter für Augenheilkunde, 2024)
This study aims to explore the associations and the underlying mechanism among dry eye disease (DED), air pollution, and meteorological conditions. DED is positively correlated with air pollutants (i.e., PM2.5, PM10, O3, NO2, CO, and SO2) and meteorological conditions (i.e., high altitude and wind speed), while negatively associated with relative humidity. Both low and high air temperatures effect DED. Atmospheric pollutants affect DED mainly through necroptosis or autophagy, inflammatory responses, and oxidative stress. Meteorological factors affect DED not only by their own affects but also by dispersing the concentration of air pollutants, and then reducing the negative exposure. In summary, this review may expand the understanding of the effects of air pollution and meteorological factors on DED and emphasize the importance of air environmental protection.
Keywords: dry eye disease; air pollution; meteorological conditions; particulate matter; mechanisms